2005
DOI: 10.3201/1102.040274
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Cryptosporidiosis Decline after Membrane Filtration of Public Water Supplies, England, 1996–2002

Abstract: Sporadic cryptosporidiosis and associated hospital admissions of children declined after membrane filtration of public drinking water supplies was introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…The risk to human health may only become apparent when this water is supplied to a large susceptible population resulting in an outbreak. It should be remembered also that the presence of oocysts in the water supply contributes to sporadic disease although the association will usually be difficult to identify except when studies have been set up specifically to look for this (Goh et al 2004;Goh et al 2005). All surface water-derived water supplies present a potential risk to human health and appropriate control measures should be in place to minimise these risks.…”
Section: Resultsmentioning
confidence: 99%
“…The risk to human health may only become apparent when this water is supplied to a large susceptible population resulting in an outbreak. It should be remembered also that the presence of oocysts in the water supply contributes to sporadic disease although the association will usually be difficult to identify except when studies have been set up specifically to look for this (Goh et al 2004;Goh et al 2005). All surface water-derived water supplies present a potential risk to human health and appropriate control measures should be in place to minimise these risks.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, epidemiology is associated with the study of epidemics and localized outbreaks (two or more associated cases). Epidemiologic study methods, however, can also be used for the study of sporadic (endemic) and pseudo-sporadic (diffuse, low-level outbreaks only identified as associated by such studies and by typing of isolates, particularly if these are unusual strains) infection that may share common features with outbreaks such as potential routes of transmission, including water (Casemore 1995;Meinhardt et al 1996;Goh et al 2004Goh et al , 2005Hunter et al 2004). The outcome of the contamination of water supply and transmission to consumers depends on complex dynamics with various, usually ill characterised, factors-the organism, the exposed persons (and their levels of immunity) and the environment (Casemore 1994(Casemore , 1995Meinhardt et al 1996).…”
Section: Definitions and General Aspects Of Immunologymentioning
confidence: 99%
“…While some studies have found a decreased risk of endemic enteric illness to be associated with improved water treatment, this and other studies have not (Hellard et al 2001(Hellard et al , 2002McConnell et al 2001;Goh et al 2005). A study in northwest England estimated a 79% reduction in the incidence of cryptosporidiosis after the introduction of membrane filtration (Goh et al 2005).…”
Section: Discussionmentioning
confidence: 94%
“…Goh et al (2005) found that microfiltration was associated with a reduction in sporadic cases of cryptosporidiosis at a United Kingdom site. Several randomized household intervention studies have been conducted in Australia, Canada and the US (Payment et al 1991;Hellard et al 2001;Colford et al 2005).…”
Section: Introductionmentioning
confidence: 97%